2020
DOI: 10.12973/eu-jer.9.2.569
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Community of Inquiry (CoI) Learning Model and Learning Style towards Social Skills

Syarifuddin Syarifuddin,
Punaji Setyosari,
Sulton Sulton
et al.

Abstract: This study aims to examine and describe the effect of the community of inquiry (CoI) learning model and learning styles on students' social skills. The sample used was a student of the faculty of education IAIM Bima Indonesian totaling 114 people, consisting of two experimental groups with 56 students and two control groups were 58 students. The community of inquiry (CoI) learning model was applied in the experimental group whereas the control group applied a cooperative learning model (comparison). This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The literature review found plentiful theoretical studies that highlight the approaches to developing the healthy lifestyle behaviours in the students (Bakouei et al, 2019;Caliskan et al, 2018;Celebi et al, 2017;Kabakci, 2019). Pedagogical literature mostly focuses on pedagogical strategies targeting the physical activity or social skills of the students and schoolchildren aimed at establishing the environment that favours their successful learning and life enjoyment (Dudley, 2011;Lander et al, 2019;Ningthoujam et al, 2017;Syarifuddin et al, 2020;Zhang, 2016). Medical sources reveal the practice of health literacy promotion through running information campaigns and individual counselling (Almutairi, et al, 2018;Hadden, 2015;Juvinyа-Canal, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review found plentiful theoretical studies that highlight the approaches to developing the healthy lifestyle behaviours in the students (Bakouei et al, 2019;Caliskan et al, 2018;Celebi et al, 2017;Kabakci, 2019). Pedagogical literature mostly focuses on pedagogical strategies targeting the physical activity or social skills of the students and schoolchildren aimed at establishing the environment that favours their successful learning and life enjoyment (Dudley, 2011;Lander et al, 2019;Ningthoujam et al, 2017;Syarifuddin et al, 2020;Zhang, 2016). Medical sources reveal the practice of health literacy promotion through running information campaigns and individual counselling (Almutairi, et al, 2018;Hadden, 2015;Juvinyа-Canal, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Medical sources reveal the practice of health literacy promotion through running information campaigns and individual counselling (Almutairi, et al, 2018;Hadden, 2015;Juvinyа-Canal, et al, 2020). The psychologies and instructors specialising in the promotion of a healthy lifestyle are attempting to prove that the outcomes of their efforts are reliant a great deal on the community influence and culture on the youth (Syarifuddin et al, 2020). For instance, Ibrahim et al (2016) found that their community-based healthy lifestyle intervention program significantly positively improved health-related quality of life (HRQoL) for not only a physical component (PCS) of it (by 6.51 points (5.21 to 7.80, p<0.001)) but for a mental component (MCS) as well (by 7.79 points (6.44 to 9.14, p<0.001)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social skills are very important learning objectives to be achieved by every student. Social skills are one of the abilities to create harmonious social relations and satisfy various parties, in the form of adjusting to the social environment and solving social problems (Setyosari et al, 2020). The formation of social skills in a child cannot be done quickly, but requires a deep process of habituation to them and this is of course integrated into every learning process and sustainable in achieving goals (Irmansyah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social skills is a behavior that needs to be learned, because it allows individuals to interact, get a positive or negative response, with an environment that includes skills in showing empathy, working together, participating in group activities, helping each other, communicating with others, negotiating, and solving problems (Pratiwi et al, 2016), (Susanti et al, 2020). Social skills is one of the abilities to create social relations that are harmonious and satisfying for various parties, in the form of adjustments to the social environment and solving social problems (Syarifuddin et al, 2020). Social skills can also influence students' learning motivation (Fang et al, 2016).…”
Section: A Introductionmentioning
confidence: 99%